The Social Effects Of The Economic Transformation In India (An Attempt At Measurement and Evaluation) - Bywalec, Grzegorz (Comparative Economic Research. Central and Eastern Europe, 2017)
One of significant and, at the same time, challenging research problems in Economics is measuring the social effect of economic growth (development). Economic growth should never be treated a goal per se. It is rational provided that it brings effects such as, generally speaking, an improvement in the standard of living. However, this is not always the case. Social sciences, including Economics, have not developed any uniform methods of measuring and evaluating such effects yet. This paper constitutes an attempt to measure and evaluate the social effects of the reforms of the Indian economy and state launched in 1991. The analysis covers a period of over twenty years. As a result of the aforementioned reforms, at the beginning of the second decade of the 21st century, India ranked third in the world in terms of GDP (based on purchasing power parity), after the USA and China. So what are the social effects of such a dynamic economic growth? For the purposes of this paper, in order to quantify and evaluate the social effects of the economic growth in India and its dynamics in the analysed time period, the author experimentally adopts a popular socio-demographic index, i.e. the average further life expectancy (e0). This constitutes the so-called natural aggregate (a micro index) applied in social development analyses. It is quite commonly used by Indian economists and statisticians, albeit it is rarely applied in European Economics. The empirical analysis of the trends in the said index proves that the rapid economic growth in India after the year 1991 has brought about substantial increases in the life expectancy of the inhabitants of the country and a diminishing of disparities in this regard on a national scale (in different cross-sections: urban-rural, females-males, as well as in the regional perspective). In the mid-2010s India is almost on a par with the countries with a medium development rate in terms of the life expectancy of its inhabitants and in some states (e.g. Kerala). the value of this index is comparable to that in the highly developed countries.